(untitled) (Journal of the Entomological Research Society, 2025)
The pleasing lacewing Dilar turcicus Hagen, 1858 is well known on the Balkan Peninsula from taxonomic and faunistic aspects, but its ecology and phenology have been poorly studied. The paper summarizes the published and new data on the distribution, phenology, ecology and altitude preferences of D. turcicus in the area. Altogether 26 unpublished records of the species are presented and a map documenting the known distribution is provided. The collecting place of D. turcicus in Serbia is the first record in the country and the northernmost locality on the Balkan Peninsula. In addition, the findings on the islands of Brač and Hvar confirm the presence of the species in Croatia after a hundred years.